2021
DOI: 10.1136/bmjopen-2020-043373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interventions based on educational technologies on the prevention of sexually transmitted infections in incarcerated women: protocol of a systematic review and meta-analysis

Abstract: IntroductionPrisons are places with high vulnerability and high risk for the development of sexually transmitted infections. World Health Agencies recommend establishing intervention measures, such as information and education, on the prevention of diseases. Thus, technologies as tools for health education have been used to reduce sexually transmitted infections. However, no systematic review has investigated the effectiveness of these interventions. Therefore, this review’s objective is to examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…9,43 Usually, healthcare professionals talk with patients about STIs focusing on preventive measures and campaigns. [44][45][46][47][48] However, the present study revealed a lack of systematic reviews focused on the communication of positive test result and post-test counseling, as well as their impact on patient's lives. To the best of our knowledge, this study represents the first systematic review to specifically investigate the literature on protocols for post-test communication of STIs and observational studies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…9,43 Usually, healthcare professionals talk with patients about STIs focusing on preventive measures and campaigns. [44][45][46][47][48] However, the present study revealed a lack of systematic reviews focused on the communication of positive test result and post-test counseling, as well as their impact on patient's lives. To the best of our knowledge, this study represents the first systematic review to specifically investigate the literature on protocols for post-test communication of STIs and observational studies.…”
Section: Discussionmentioning
confidence: 75%
“…The process of conveying a “bad diagnosis” is an important subject, as it can have significant psychological and emotional impacts on patients, particularly regarding their uncertainties in the present and future 9,43 . Usually, healthcare professionals talk with patients about STIs focusing on preventive measures and campaigns 44–48 . However, the present study revealed a lack of systematic reviews focused on the communication of positive test result and post‐test counseling, as well as their impact on patient's lives.…”
Section: Discussionmentioning
confidence: 80%
“…Screening can refer to an organized, systematic, facility-wide program, or a single intervention. 15 Surveillance is the collection, analysis, and interpretation of information on the health status of a population-in this case, incarcerated persons-to provide early warning of disease outbreaks and to monitor disease burden over time. 1 There will be no limitations on the type, frequency, or mode of delivery of interventions investigated in the studies.…”
Section: Interventionsmentioning
confidence: 99%
“…Interventions will include screening for STIs and/or BBVs, STI case management programs, surveillance clinics, new models of care, condom and dental dam promotion, pharmaceutical prophylaxis programs, health promotion, and education programs. Screening can refer to an organized, systematic, facility-wide program, or a single intervention 15 . Surveillance is the collection, analysis, and interpretation of information on the health status of a population—in this case, incarcerated persons—to provide early warning of disease outbreaks and to monitor disease burden over time 1 .…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation